Tree species mixing causes shifts in nitrogen acquisition and utilization strategies of Mongolian pine and Simon poplar - Li, Xin; Zeng, De-Hui; Sheng, Zimeng; Sun, Yanzhen; Lin, Guigang (Ecological processes, 2025)
Background Establishing mixed-species plantations is increasingly recognized as an important silvicultural measure because they are more productive than monocultures. This over-yielding is attributed to the complementary resource use between component tree species, yet it remains largely unknown whether and how component tree species adjust nutrient acquisition and utilization strategies to achieve complementary nutrient use. Here, we measured soil nitrogen (N) availability and transformation rates, leaf N resorption efficiency and proficiency, and nine root morphological, physiological and mycorrhizal traits tightly related to N acquisition in 20-year-old pure and mixed stands of Pinus sylvestris var. mongolica (Mongolian pine) and Populus simonii (Simon poplar), northeast China. Results Tree species mixing had negative effects on soil nitrate concentration and net N mineralization rate, but had positive effects on absorptive fine root biomass. Compared to growing alone, Mongolian pine in mixed stands had higher leaf N resorption efficiency, and produced more absorptive fine roots with more-efficient morphological features in nutrient acquisition characterized by higher specific root length and lower root tissue density. Additionally, Simon poplar had greater root length density, root area index, and the relative abundance of ectomycorrhizal fungi with genetic potential to produce class II peroxidases in mixed than pure stands. Conclusions These findings highlight that component species express high plasticity in nutrient acquisition and utilization traits in response to tree species mixing, and suggest that this high plasticity could be responsible for the over-yielding of mixed-species plantations.